Pengaruh Gaya Kepemimpinan, Motivasi, dan Reward Terhadap Kinerja Karyawan (Studi Kasus di Pondok Pesantren Modern Nurussalam Sidogede OKU Timur Sumatera Selatan) - Facktian Lampita Suryani; Hasanah Hasanah; Imam Muhtadin (STKIP Pesisir Selatan, 2024)
Human resources institutions or foundations are very important things, which must have proficiency, skills, competence, and quality in carrying out their role as employees or labor. The purpose of this study was to explain the effect of Leadership Style, Motivation, and Reward on Employee Performance at the Nurussalam Modern Islamic Boarding School Sidogede OKU East South Sumatra. This type of research is quantitative. The population in this study were all employees at the Modern Nurussalam Islamic Boarding School Sidogede OKU East South Sumatra. Data collection using saturated sampling distributed to 84 respondents. Data collection techniques in this study were questionnaires and documentation with multiple regression analysis, with the help of SPSS software. The results of this study indicate that Leadership Style, Motivation, and Reward simultaneously affect employee performance. The Asymp.Sig (2-tailed) value of 0.79 proves that Leadership Style, Motivation and Reward are 79% of the influence on employee performance. While the remaining 21%, explained by other variables outside this study. Partially, Leadership Style has a significant effect on employee performance of 8.195, Motivation has a significant effect on employee performance of -3.393. And Reward has a significant effect on employee performance by 2,073.